If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying -2x^{2}+ 4x + 12 = 0 Reorder the terms: 12 + 4x + -2x^{2}= 0 Solving 12 + 4x + -2x^{2}= 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(6 + 2x + -1x^{2}) = 0 Ignore the factor 2.## Subproblem 1

Set the factor '(6 + 2x + -1x^{2})' equal to zero and attempt to solve: Simplifying 6 + 2x + -1x^{2}= 0 Solving 6 + 2x + -1x^{2}= 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -6 + -2x + x^{2}= 0 Move the constant term to the right: Add '6' to each side of the equation. -6 + -2x + 6 + x^{2}= 0 + 6 Reorder the terms: -6 + 6 + -2x + x^{2}= 0 + 6 Combine like terms: -6 + 6 = 0 0 + -2x + x^{2}= 0 + 6 -2x + x^{2}= 0 + 6 Combine like terms: 0 + 6 = 6 -2x + x^{2}= 6 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x^{2}= 6 + 1 Reorder the terms: 1 + -2x + x^{2}= 6 + 1 Combine like terms: 6 + 1 = 7 1 + -2x + x^{2}= 7 Factor a perfect square on the left side: (x + -1)(x + -1) = 7 Calculate the square root of the right side: 2.645751311 Break this problem into two subproblems by setting (x + -1) equal to 2.645751311 and -2.645751311.## Subproblem 1

x + -1 = 2.645751311 Simplifying x + -1 = 2.645751311 Reorder the terms: -1 + x = 2.645751311 Solving -1 + x = 2.645751311 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 2.645751311 + 1 Combine like terms: -1 + 1 = 0 0 + x = 2.645751311 + 1 x = 2.645751311 + 1 Combine like terms: 2.645751311 + 1 = 3.645751311 x = 3.645751311 Simplifying x = 3.645751311## Subproblem 2

x + -1 = -2.645751311 Simplifying x + -1 = -2.645751311 Reorder the terms: -1 + x = -2.645751311 Solving -1 + x = -2.645751311 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -2.645751311 + 1 Combine like terms: -1 + 1 = 0 0 + x = -2.645751311 + 1 x = -2.645751311 + 1 Combine like terms: -2.645751311 + 1 = -1.645751311 x = -1.645751311 Simplifying x = -1.645751311## Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.645751311, -1.645751311}## Solution

x = {3.645751311, -1.645751311}

| 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 | | X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 | | 12a^4b^3=0 | | 108x^4+360x^3+447x^2+245x+50=35 | | -35x^2-5x+30=0 | | 12x+2=3x^2 | | 2x^2+3x+5=0 | | (12x^2-3x-8)-(4x^2+5)= | | 5n+6n^4+3n-8n^4+n= | | 3n-2n^4+n+7n^4-2n= | | 12n-2n^4-10n-2n^4+n= | | X^2+16x+42=0 | | x^2+2x-288=0 | | 2x^2+3x-44=0 | | X^2+10x+22=6 | | x^5+x^4+x^3+x^2+x+3=0 | | x^2+6x-65=0 | | 56x+8x^2=0 | | x^2+6x+8=0 | | x^2+16x=-7 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions